THE EFFECT OF IMPLEMENTING GREEN ACCOUNTING AND DISCLOSURE OF SUSTAINABILITY REPORTING ON PROFITABILITY - Sri Mulyati; Nur Khalimatusadiah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This research aims to test the application of Green Accounting and Sustainability Reports to Profitability. The population in this study consists of plantation sector companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange in 2021-2022. This research uses multiple regression analysis and different tests using the SPSS program using descriptive quantitative methods, namely by describing data and facts from the results of Green Accounting calculations using the Duumy method, Sustainability Reports using the Sustainability Report Disclosure Index (SRDI) and Profitability is measured using Return On Assets (ROA). The results of this research show that the independent variables, namely Green Accounting (GA) and Sustainability Report (SR) have no effect on the dependent variable Profitability.